Addition Of Chain Extender To Improve Flexible Polyurethane Foam Characteristics Of Palm Oil Polyol - Novizar Nazir; Syukri Arief; Yurniwati; Neswati Neswati (Asia Pacific Network for Sustainable Agriculture, Food and Energy (SAFE-Network), 2023)
The use of 100% palm oil polyol without the addition of a chain extender produced foam which initially expands and then collapses so that the resulting foam has tight pores, dense texture, and brittle (brittle). It was necessary to use a chain extender to improve the flexible properties of the foam. This study aimed to examine the ratio of palm oil polyols with a chain extender to produce flexible polyurethane foam with good characteristics. The treatment of this study was a combination of types and comparisons of palm oil polyols with chain extenders which were carried out 3 times, consisting of factor A = type of chain extender (diethylene glycol (DEG), diethanolamine (DEA), and polyethylene glycol (PEG)-400) and factor B = ratio of palm oil polyols. with a chain extender (80%:20%; 70%:30%; 60%:40%; 50%:50%). The obtained foam was observed visually, foam development, and foam density. The best sample for each type of extender was analyzed by FTIR. The results showed that 40% PEG-400 has succeeded in producing flexible polyurethane foam with higher expansion (291.22%), lower density (29 kg/m3), and visually has the best flexible properties. Based on FTIR analysis, the use of PEG-400 in the polyol system can increase the reactivity of palm oil polyols to isocyanates.